2016
DOI: 10.1364/ol.41.001781
|View full text |Cite
|
Sign up to set email alerts
|

Generation of orthogonally polarized self-mode-locked Nd:YAG lasers with tunable beat frequencies from the thermally induced birefringence

Abstract: The simultaneous self-mode-locking of two orthogonally polarized states in a Nd:YAG laser is demonstrated by using a short linear cavity. A total output power of 3.8 W can be obtained at an incident pump power of 8.2 W. The beat frequency Δfc between two orthogonally polarized mode-locked components is observed and measured precisely. It is found that the beat frequency increases linearly with an increase in the absorbed pump power. The origin of the beat frequency can be utterly manifested by considering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Thévenin et al reported a first dual-polarization ML laser with Nd:YAG crystal, synchronously generating two-frequency combs associated with the two polarization eigenstates [24]. Recently, Cheng et al obtained monolithic dual-polarization self-ML Nd:YAG crystal 946 nm lasers with chaotic dynamics and tunable beat frequencies [25,26]. Liang et al reported an orthogonally polarized ML laser with an Nd:YVO 4 crystal, with a wavelength of 1342 nm and pulse repetition rates up to 6.45 GHz [27].…”
Section: µM Vector Mode-locked Pulses From Tm:y O 3 Ceramics Lasermentioning
confidence: 99%
“…Thévenin et al reported a first dual-polarization ML laser with Nd:YAG crystal, synchronously generating two-frequency combs associated with the two polarization eigenstates [24]. Recently, Cheng et al obtained monolithic dual-polarization self-ML Nd:YAG crystal 946 nm lasers with chaotic dynamics and tunable beat frequencies [25,26]. Liang et al reported an orthogonally polarized ML laser with an Nd:YVO 4 crystal, with a wavelength of 1342 nm and pulse repetition rates up to 6.45 GHz [27].…”
Section: µM Vector Mode-locked Pulses From Tm:y O 3 Ceramics Lasermentioning
confidence: 99%
“…And the lasing mode is split into two polarization states with the aid of birefringent effect involving natural birefringence, 17 photoelastic effect, 18,19 electro-optical effect, 20 and thermo-optical effect. 21 Therefore, the frequency difference is susceptible to external forces, and frequencies of two single-modes could not be tuned independently. Moreover, the maximum frequency difference of dual-frequency is ultimately limited by its relatively small longitudinal mode interval of the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Based on such design, it is a prerequisite to make the single longitudinal mode operate first with a mode selection element. And the lasing mode is split into two polarization states with the aid of birefringent effect involving natural birefringence, 17 photoelastic effect, 18 , 19 electro-optical effect, 20 and thermo-optical effect 21 . Therefore, the frequency difference is susceptible to external forces, and frequencies of two single-modes could not be tuned independently.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been paid to study the orthogonally polarized dualwavelength mode-locked lasers for practical applications including asynchronous optical sampling, control of magnetization, laser spectroscopy, and optical communication [8][9][10][11][12]. To realize an orthogonally polarized dual-wavelength laser [13][14][15][16][17], it is prerequisite to balance the gain-to-loss conditions for the orthogonally polarized states. For a conventional acut Nd:YVO 4 crystal where the π-polarization (parallel to the crystallographic c axis) predominates the laser oscillation, an additional intracavity birefringent element [18][19][20] or a wedged gain crystal [21,22] is frequently required to balance the gain competition between the π-and σ-polarization (perpendicular to c axis) states.…”
Section: Introductionmentioning
confidence: 99%